2003
DOI: 10.1002/art.10844
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic markers in the 5′‐flanking region of ANKH are associated with ankylosing spondylitis

Abstract: Objective. To use a candidate gene approach for the identification of genetic markers that are significantly linked to and associated with ankylosing spondylitis (AS).Methods. We searched for novel polymorphisms in the ANKH gene (human homolog of the murine progressive ankylosis gene) and genotyped 2 polymorphic sites, one in the 5-noncoding region and the other in the promoter region of ANKH, using DNA from affected (n ‫؍‬ 273) and unaffected (n ‫؍‬ 112) individuals from 124 AS families. We used these ANKH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 27 publications
(39 reference statements)
2
43
1
2
Order By: Relevance
“…The best explanation for the discrepancies is that the contribution of each non-MHC gene to the overall susceptibility to AS is likely small ( s Ͻ 2.0), and the number of sibpairs examined by our group (n ϭ 244) and by Laval et al (n ϭ 255) (10) may not, when examined individually, provide adequate power to discern such "small effect" genes. Further evidence for this is provided by the identification of significant association of AS in our families with the ANKH gene encoded on chromosome 5p (21), despite the fact that this region was not identified by the ABI PRISM linkage map MD-10 marker panel used in this study. Alternatively, the marker density could be increased, using microsatellite markers spaced much more closely.…”
Section: Discussionmentioning
confidence: 79%
“…The best explanation for the discrepancies is that the contribution of each non-MHC gene to the overall susceptibility to AS is likely small ( s Ͻ 2.0), and the number of sibpairs examined by our group (n ϭ 244) and by Laval et al (n ϭ 255) (10) may not, when examined individually, provide adequate power to discern such "small effect" genes. Further evidence for this is provided by the identification of significant association of AS in our families with the ANKH gene encoded on chromosome 5p (21), despite the fact that this region was not identified by the ABI PRISM linkage map MD-10 marker panel used in this study. Alternatively, the marker density could be increased, using microsatellite markers spaced much more closely.…”
Section: Discussionmentioning
confidence: 79%
“…Since ANKH is a growth factor (17) and an androgenresponsive gene (18), it is possible that cytokines generated by inflammation dysregulate the expression of ANKH, resulting in neo-ossification. We previously tested whether ANKH is one of the susceptibility genes for AS (19), and we later showed that ANKH is linked to, and associated with, AS in 201 Caucasian multiplex families (20). However, another study concluded that ANKH did not significantly contribute to susceptibility or specific disease expression in AS patients from the UK (21).…”
Section: Conclusion Our Results Indicate That the Tnap Haplotype Rs3mentioning
confidence: 99%
“…However, weakly positive findings have been reported by some authors, and the association may be strong in women 7,8 . Pimentel-Santos, et al showed that ANKH is not a major determinant of susceptibility to AS and ANKH polymorphism does not influence AS severity 1 .…”
Section: Ankh and Renal Stone Formation In Ankylosing Spondylitismentioning
confidence: 79%